2003
DOI: 10.1021/jp030998v
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of the Electronic State, Geometry, and Harmonic Frequencies for Linear CnP2 Clusters:  A Comparison with CnN2

Abstract: Linear C n N2 and C n P2 clusters, in the lowest energy singlet and triplet states, were studied using the B3LYP/ 6-311G** theoretical method for n = 5−10 and the B3LYP/aug-cc-pVTZ method for n = 5−8. Harmonic frequencies are also reported. Clusters with odd numbers of carbon atoms have lower lying triplet ground states, while those with even numbers of carbons are singlets. The energies of the acetylenic singlet ground states are approximately 2.5 eV below those of the lowest triplet state, while the triplet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Therefore, the absence of C x N y – ( y ≥ 2) clusters in the distribution generated from the ablation of 1 is not due to the lack of stability of these species. Indeed, a number of computational studies have predicted the stable structures of many clusters seen in this study. ,,,,, Mogren and co-workers found that the lowest energy structures for the C x N y – clusters with ( x + y ) ≥ 5 and y ≥ 2 were bent or cyclic . The more abundant clusters we observe in this region coincide with these highly stable cyclic structures.…”
Section: Results and Analysissupporting
confidence: 55%
“…Therefore, the absence of C x N y – ( y ≥ 2) clusters in the distribution generated from the ablation of 1 is not due to the lack of stability of these species. Indeed, a number of computational studies have predicted the stable structures of many clusters seen in this study. ,,,,, Mogren and co-workers found that the lowest energy structures for the C x N y – clusters with ( x + y ) ≥ 5 and y ≥ 2 were bent or cyclic . The more abundant clusters we observe in this region coincide with these highly stable cyclic structures.…”
Section: Results and Analysissupporting
confidence: 55%
“…A structural study of the NCCCN cluster at the CCSD(T)/aug-cc-pVTZ//B3LYP/6-31+G* level indicted that the linear centro symmetric 3 Σ g − state is more stable than the 1 A 1 state by 18 kcal/mol. , In three studies by Chuchev and BelBuruno of some carbon−nitrogen clusters, the authors concluded that in general the odd-numbered carbon clusters have triplet states and are more cumulenic, whereas even numbered carbon clusters have singlet states and are acetylenic. These assumptions are confirmed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important clusters is the carbon−nitrogen clusters. Carbon−nitrogen clusters are abundant in interstellar space and in planetary atmospheres, for example, Titan, and have unusual reactivity and thus are difficult to study on earth. It has also been reported, theoretically, that carbon−nitride films are harder than diamond. There are several reports of the structure of carbon−nitrogen clusters where the electronic, vibrational, rotational, and structural properties of small, medium, and large sized carbon−nitrogen clusters are investigated. Briefly, Wang et al performed HF calculations on linear C n N anion clusters and showed that odd- n isomers are much more stable than even- n isomers, in good agreement with the mass spectrometry studies for the lowest-lying linear and cyclic structures.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the currently available data for heteroatom−carbon clusters are for linear, doubly terminated XC n X clusters in which the heteroatoms are from Groups IVB−VIIB 16 or the transition metals . Detailed computational results for carbon clusters containing N, P, O, S, and Se have indicated that these atoms participate in the π-electron system of the clusters and that linear structures with terminal heteroatoms are lowest in energy. The heteroatom in the current work is boron, typically used as a p -type dopant in semiconductor studies. The valence shell of boron has one less electron than the carbon atoms in the cluster.…”
Section: Introductionmentioning
confidence: 98%